Social stigma and media in the context of criminal proceedings, from an ethical, constitutional and legal glimpse in Colombia (2014)
The fundamental right to freedom of expression includes the representation and dissemination of ideas and opinions, information transmission and its reception, as well as the foundation of mass media. From the above, it is attributed to the mass media, the fulfillment of the duty of social responsibility, in which there are other duties and obligations both constitutional and legal and ethical origin that in their exercise or activity must observe. Requirements that achieve a greater degree of rigor, when the media disseminates information on legal issues and particularly those of a criminal nature, which due to their social implications and stigmatization which expose the protagonists of communication, it has to meet the objective duty of care, because the right here commented, like others, has no absolute character and therefore it cannot violate legally protected interests such as moral integrity.